Superspin glass state in a diluted nanoparticle system stabilized by interparticle interactions mediated by an antiferromagnetic matrix. (8th December 2016) - Margaris, G; Vasilakaki, M; Peddis, D; Trohidou, K N; Laureti, S; Binns, C; Agostinelli, E; Rinaldi, D; Mathieu, R; Fiorani, D
Abstract: In nanoparticle systems consisting of two magnetic materials (bi-magnetic nanoparticles or nanoparticles embedded in a magnetic matrix), there is a constantly growing interest in the investigation of the interplay between interparticle interactions and the nanoparticle-matrix interface exchange coupling, because of its enormous impact on a number of technological applications. The understanding of the mechanisms of such interplay is a great challenge, as it would allow controlling equilibrium and non-equilibrium magnetization dynamics of exchange coupled nanoparticles systems and finely tuning their anisotropy. Here, we provide evidence that this interplay leads to a collective superspin glass (SSG) behavior in a system of diluted ferromagnetic (FM) nanoparticles embedded in an antiferromagnetic (AFM) matrix (5% volume fraction of Co particles in Mn film matrix). We have developed a novel mesoscopic model to study the influence of interparticle interaction on the exchange bias (EB) and the dynamical behavior of assemblies of FM nanoparticles embedded in a granular AFM matrix. Our mesoscopic model is based on reducing the amount of simulated spins to the minimum number necessary to describe the magnetic structure of the system and introducing the adequate exchange parameters between the different spins. The model replicates remarkably well the observed static and dynamical SSG properties as well as the EB behavior. In addition, the proposed model well explains the role of the significant Co/Mn alloying and of the granularity of the matrix in mediating interparticle interactions through exchange and dipole–dipole coupling between the uncompensated moments of its grains and the exchange interaction at the Co/Mn interface.